Identification method of wheel-rail two-point contact state in switch area - Ping Lu; Xinyi Li; Dabin Cui; Boyang An; Wenpeng Jiang (Scientific Reports)
Abstract Two-point contact is one of the fundamental problems of wheel-rail contact in switch area. The contact state and the distribution of forces are complex and essential points in wheel-rail relationship. Given the problem that the current dynamic wheel-rail contact state is challenging to detect, a theory to detect the two-point contact state of the wheel-rail in switch area using a discrete gauge column was presented and proved in the finite element model. This paper derived the relationship between strain gauge position and stress using a modified rail model. The patch scheme was determined using the rail waist bending moment difference method to achieve decoupling of the bridge circuit of the force measurement columns. The bridge circuit was calibrated by means of the modified theoretical calibration method, and the circuit test data was obtained for the two-point contact condition in the switch area. The study compared the results obtained from the wheel-rail column finite model and circuit test data for two-point contact conditions, demonstrated the method’s ability to identify the two-point contact state and the wheel-rail force distribution characteristics in the switch area. The results show that the method can identify the two-point contact state in switch area and distribute characteristics of the wheel-rail force. And the wheel-rail contact point position can be deduced accurately according to the wheel-rail force. This test method provides a test verification scheme for wheel-rail two-point rolling contact theory and a new technology for the dynamic force testing of wheel-rail in switch area.